Blockchain-IoT Healthcare Applications and Trends: A Review - Wafaa A. N. A. Al-Nbhany; Ammar T. Zahary; Asma A. Al-Shargabi (IEEE Access)
Despite the increasing reliance on the Internet of Things (IoT) as a basic infrastructure for future applications. Integrating blockchain technology with IoT extensively helps provide basic security requirements owing to the built-in security structure of the blockchain. Healthcare IoT applications are one of the industries that will be revolutionized by using IoT-blockchain technology. This review aims to provide an integrated understanding of blockchain IoT healthcare applications. The methodology of our paper is to review the literature from 2018 to 2023, paying more attention to research that intersects and integrates IoT, Blockchain, and healthcare applications. This review addresses IoT-based blockchain types and technologies, healthcare applications, sensors, hardware tools, application databases, programming languages, software tools, challenges and open issues, and solutions with their advantages and limitations. We then compared our work with existing works on common metrics. The study in this paper includes 14 blockchain IOT healthcare applications: remote patient monitoring, patient tracking, disease prediction, tracking COVID-19, image retrieval, security of medical records, smart telemedicine, securing the Internet of Medical Things, big data, blockchain and sensors, accurate medical decisions, health monitoring, tracking soldiers, and solar energy.